Mushaf Lipat Abu: Suntingan, Terjemahan, dan Keutamaan serta Manfaat Teks - Romadhoni, Mohammad Hasbi; Cika, I Wayan (Humanis; Vol 26 No 1 (2022)DO - 10.24843/JH.2022.v26.i01.p11, 2022)
Mushaf lipat Abu is a manuscript given by a collector from Jakarta named Abu in 2018. The purpose of this paper is to findi out the contents and describe and introduce the mushaf lipat because of the uniqueness of the manuscripts and to add studies to the Nusantara manuscripts using philological theory. Mushaf lipat Abu was studied using philological theory and translation theory. The method used for data collection is a catalog study method and a field study method with a note-taking technique whose purpose is to find a manuscript whether there are variants. The method used in analyzing the data is the standard method of single manuscript edition and the method of presentation is descriptive analytical method. The results showed that the mushaf lipat is a codex unicus because it is not contained in the catalog that the researcher refers to. Mushaf lipat consists of two main materials, namely wood and paper, mushaf lipat contains four letters in the Qur'an, namely Al-Fatihah as an opening letter, As-Sajdah, Ad-Duha, and Al-Ikhlas.